Leites fermentados probióticos produzidos a partir de bactérias ácido-lácticas e adicionados de concentrado protéico de soro lácteo: características físico-químicas, microbiológicas e sensoriais - Roane Pena Viegas (2008)
The manufacture of fermented dairy products in Brazil is based on the use of starter cultures, which are commercialized by foreign companies. In spite of that, there is a great potential to exploit indigenous lactic acid bacteria, isolated from artisanal dairy products. Therefore, this work was carried out in order to produce fermented milks using lactic acid bacteria, isolated from coalho cheese artisanaly made of raw milk in Pernambuco state, Brazil. Weissella confusa and Lactobacillus acidophilus strains, isolated from that food and previously tested according to some probiotic features were used isolatedely or in association to ferment milk, suplemented or not by whey protein concentrate (WPC). The viability of both cultures as well as the physical-chemical and microbiological characteristics of the fermented milks stored at 8-10ºC were studied during 40 days. The obtained products were also submitted to a sensorial evaluation on days 10th and 40th after their preparation. Fermentation profiles plotted from results of pH, titratable acidity (%), and bacterial counts showed higher values of titratable acidity and lower values of pH in products fermented by Lactobacillus acidophilus. Desirable counts of microorganisms, considering their probiotic potential and higher than the minimum required by the Brazilian legislation, were recorded in all fermented milks throughout time. Products obtained by Weissella confusa demanded a longer fermentation time, irrespectively of WPC adding; while those fermented by both bacteria required shorter times of production. All the products showed minimum counts of viable bacteria at 108CFU/g throughout the 40 days of storage at 8-10ºC. WPC adding did not cause variation in the flavor of the obtained products (p>0.05). Flavor of Lactobacillus acidophilus fermented milk was considered better on day 10th and 40th. Indeed, the results pointed to a future probability of producing fermented milks using the tested cultures, preferably in association and without WPC adding, presenting a shelf life around 40 days if properly refrigerated